Phenotypic plasticity in Bromelia serra Griseb.: morphological variations due to plant size and habitats with contrasting light availability - Barberis, Ignacio Martín; Cárcamo, José María; Cárcamo, Juan Ignacio; Albertengo, Juliana (Revista Brasileira de Biociências, 2017)
In the understory of the Schinopsis balansae Engl. forests of the Wet Chaco there are dense populationsof Bromelia serra. The individuals of this strictly terrestrial bromeliad grow in the sun as well as in the shade of the understory.Studies carried out with a facultative epiphytic bromeliad, Aechmea distichantha Lem., which also lives in the understory of theseforests and whose foliar bases form a tank (phytotelmata), showed the existence of differences in plant architecture and biomassallocation due to plant size (apparent phenotypic plasticity) and to environmental conditions (true phenotypic plasticity). Thus,to evaluate whether the architecture and biomass allocation of a strictly terrestrial bromeliad are also affected by habitat and byplant size, we selected 22 plants of B. serra from open areas and 22 from the understory. The selected plants covered the wholerange of plant size. For each plant, we characterized its rosette (height, diameter and number of leaves) and measured the lengthand width of the longest leaf. The plants were split into stem and leaves (sheaths and blades), weighed, and then several biomassallocation indexes were derived. At a similar biomass, plants growing in the sun had shorter leaves, with a lower length: widthratio than those from the understory, but there were no differences between habitats with regard to plant height, diameter ordifferent biomass fractions. These results suggest that B. serra (a strictly terrestrial bromeliad) shows a high apparent plasticityin most variables, but low true phenotypic plasticity in response to environmental differences.